Near-infrared spectroscopy as a potential method for routine sediment analysis to improve rapidity and efficiency - Malley, Diane F. (Water science and technology, 1998)
The potential for improvement in the rapidity, cost-effectiveness, and efficiency of sediment analysis by the application of near-infrared reflectance spectroscopy (LAIRS) is recognized. The rapid (< 2 min), non-chemical, non-destructive analytical technique of near-infrared (700 – 2500 nm) spectroscopy combines applied spectroscopy and complex statistics. It has been used for the experimental analysis of various constituents and functions of soils since the 1960s, and applications for the analysis of sediments are currently being explored. For application of NIRS, sediment samples require little preparation, other than drying, and the samples are not subject to the manipulations of conventional analytical techniques. The spectral information recorded in a 2 min scan can be used to predict numerous constituents and parameters on the samples once appropriate calibration equations have been prepared from sets of samples analyzed by both NIRS and conventional analytical techniques. Constituents and properties of soil and/or sediment analyzed by NIRS technology include moisture, organic matter content, organic C, CO3=, N, P, S, K, Ca, Mg, clay content, humic acids, lignin, cellulose, metal oxides, heavy metals, aggregate size, and inferred past pH of lakes. Several areas are identified where further research is needed to prepare for the application of NIRS to the routine analysis of sediments.